Narrative based medicine. An action research project to develop group education and support for bilingual health advocates and elderly South Asian patients with diabetes - Greenhalgh, T; Collard, A; Begum, N (2005)
The objective of this study was to develop bilingual health advocate (BHA)-led group education and support groups for South Asian patients with diabetes, based on a storytelling format. The design and setting were action research in a deprived inner London district. The research team worked developmentally with BHAs, service users and other stakeholders to assess need, train staff, and set up and evaluate the storytelling groups. Stories were chosen as the main vehicle for education because of their universal appeal, memorability, holistic perspective, ethical dimensions, and potential for multiple interpretations. Key challenges in the project were: high burden of need; multiple stakeholders; a shifting baseline of policy directives; frequent staff changes; resource constraints; and resistance of top and middle management to new service models. These difficulties made progress slow, and several early initiatives failed to take root. However, we succeeded in developing a nationally accredited training programme ('Storytelling for group work in health and care') for BHAs, and in supporting the graduates from this course to set up two groups for South Asian patients with diabetes - one in a hospital and one in a community centre. The patient storytelling groups, once established, were popular and well evaluated. Blood glucose levels in regular attenders fell, but changes did not reach statistical significance. An action research approach allowed us successfully to develop an innovative training programme for BHAs and support them in developing and mainstreaming new service models. BHA-led diabetes storytelling groups, supported by health professionals, are feasible and popular with non-English speaking Asian patients. Their impact on diabetes outcomes should now be formally evaluated in clinical trials. Copyright © 2005 John Wiley and Sons, Ltd.